Hybrid Charge‐Storage Route to Nb2CTx MXene as Anode for Sodium‐Ion Batteries. Issue 3 (23rd January 2020) - Du, Li; Duan, Huanhuan; Xia, Qi; Jiang, Chan; Yan, Yurong; Wu, Songping
Abstract: A facile hydrothermal approach has been successfully adopted to synthesize two‐dimensional Nb2 CTx MXene, targeting sodium storage approach in two‐dimensional MXene. As an anode material for sodium‐ion batteries (SIBs), as‐prepared Nb2 CTx MXene delivered a stable electrochemical performance of ∼102 mA h g −1 after 500 cycles at a current density of 1.0 A g −1 . Further, the full cell comprising of Na3 V2 (PO4 )3 @C cathode and Nb2 CTx MXene anode also rendered a reversible capacity of 181 mA h g −1 at a current density of 100 mA g −1 after 50 cycles. The good sodium storage could be ascribed to the contribution of hybrid pseudocapacitance, effectively promoted charge storage, unique layered structure and expedited dynamic diffusion of ions. Accordingly, these facts enabled the Nb2 CTx MXene to be a promising candidate as an anode material for sodium‐ion batteries. Abstract : 2D Nb2 CTx MXene delivered a reversible capacity of 102 mA h g −1 at a rate of 1.0 A g −1 after 500 cycles in half cell and 181 mA h g −1 at a rate of 100 mA g −1 after 50 charge/discharge cycles in full cell for SIBs. An investigation into the charge‐storage mechanism exhibited the emergence of hybrid pseudocapacitance, i. e., intercalation pseudocapacitance at the low potential and the surface‐controlled pseudocapacitance at the high potential in the SIBs.